IFPRI Forum: Wanted, Good jobs for fighting poverty - International Food Policy Research Institute (International Food Policy Research Institute, 2009)
The current global recession is leading to millions of job losses around the world, pushing some people deeper into poverty and nudging others into poverty for the first time. How can governments and others in developing countries create good jobs to fight poverty and hunger both now and in the long term?